Vibratory energy flux study in a hermetic compressor by statistical energy analysis - W. A. Barbosa; A. Lenzi; P.H. T. Zannin (Archives of Acoustics)
This paper presents a study of the vibratory energy transmission from the block to the shell of a hermetic compressor by the statistical energy analysis. The loss factor and modal density have been obtained experimentally. The vibratory energy of the block and shell, and the sound power radiation were also measured. The coupling loss factors from the block to shell and from the shell to the reverberation chamber have been calculated from the parameters above.